Critical Success Factors for Adopting Enterprise Architecture Metamodel in the Health Sector: Literature Review - Makola, David; Hotti, Virpi (Journal of Health Informatics in Africa, 2013)
Background and Purpose: Metamodels can be used as templates for describing models. In the context of the government enterprise architecture (GEA), the metamodels or metamodel-based reference models are primarily used to execute national strategic objectives in information systems. For example, if a National Health Insurance (NHI) service is to be delivered to approximately 400 government hospitals and 4000 clinics in South Africa, reference models (e.g. Business Information Reference Model for Health) will have to be seriously considered. This approach will require the proper definition of metamodels or metamodel-based reference models. The main purpose of this paper is to report the critical success factors (CSFs) for adopting enterprise architecture (EA) metamodels in the health sector. Methods: The latest scientific literature based on the adoption of EA metamodels in the health sector was reviewed. The guidelines of the systematic literature review were partly adapted to organize the search. Results: Queries made from the abstracts of eight digital libraries in September 2013 produced 31 hits. No papers were found on critical success factors for adopting EA metamodel in the health sector. Conclusions: Governments are adopting EA for implementing their strategies and for improving production of services, especially in the health sector. However, there is little or no scientific research done on the adaptions of EA metamodels in the health sector. Keywords: Enterprise Architecture (EA), Metamodel